EFL Students' Anxiety in Speaking English: Factors and Strategies - Masrurotul Ajiza; Arum Putri Rahayu; Setiawati; Tri Rohani; Dini Deswarni (English Language Education Department, Universitas Majalengka, 2024)
Anxiety has a big role in affecting students' performance in learning English, especially in speaking class. This study aimed to answer three questions: (1) the anxiety level the EFL students got in a speaking class, (2) some factors influence it, and (3) some strategies that can be used to minimize the level of students’ anxiety. This research used a qualitative approach by adopting a questionnaire as an instrument. The participants of this study were 113 students; 68.1% female and 31.9% male students; from 4 different universities in Indonesia from different departments (an English and non-English departments). The results of this study showed that the student’s level of anxiety was still high which was affected by internal and external factors. Those factors tended to decide the level of their anxiety. In addition, this study also showed some suggestions that can be used as strategies to minimize the level of the student’s anxiety.